Co-gasification — strategic route in the utilization of polymeric wastes - Kijeński, J.; Kijeńska, M.; Migdał, A. (Polimery, 2014)
An analysis of the concepts of utilization of post-consumer waste polymer materials from the viewpoint of global demand and supply of energy and raw materials, an increasing waste plastics deposition in and out of waste dumps as well as of European Union priorities has been presented. The possibility of the realization of a series of preferred solution proposals was discussed. The lack of concepts of the systematic, immediate and future actions to resolve the problem of polymer waste was indicated. The implementation conditions and advantages of the gasification and co-gasification of waste polymers with coal, biomass and other waste materials as a future, long-lasting solution capable of providing a uniform, standardized high-energy fuel to modern energy sector were emphasized. These methods can also constitute a raw material base for (autothermal) alternative petrochemistry — a highly effective second generation raw material recycling process.